Understanding the Spatial Heterogeneity of CO2 and CH4 Fluxes from an Urban Shallow Lake: Correlations with Environmental Factors - Zhenhua Zhao; Dan Zhang; Wenmei Shi; Xiaohong Ruan; Jie Sun (Journal of Chemistry)
The spatial variability of carbon dioxide (CO2) and methane (CH4) fluxes across water-air interface in Xuanwu Lake was investigated in two seasons. Due to anthropogenic disturbances, the environmental factors and the fluxes of CO2 and CH4 in lake showed obvious spatial and seasonal variability; their average fluxes in summer are significantly higher than those in autumn. The fluxes in heavy pollution sites with high concentrations of nitrogen and phosphorus nutrient in summer were 3.9 times (142.14 : 36.07 mg·m−2·h−1) for CO2 and 22.3 times for CH4 (6.46 : 0.29) higher than those in little pollution sites. In autumn, they were 12.3 times and 7.1 times higher, respectively. Anthropogenic disturbance and heavy pollution increased their fluxes, but aquatic plants reduced the emission of CO2. Except the sampling site with flourishing lotus, most of sampling sites without aquatic plant are the emission source of CO2 and CH4. The correlation analysis, multiple stepwise regression, and redundancy analysis showed the key environmental factors for CO2 including temperature (T), pH, chemical oxygen demand (CODMn) in water, organic matter (OM), total nitrogen, and ammonia nitrogen in water and sediment. As for CH4, the key environmental factors include turbidity, oxidation-reduction potential, dissolved oxygen, CODMn, and T in water and OM and N-NH4+ in sediment.